2017
DOI: 10.1016/j.jmbbm.2017.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Free energy analysis of cell spreading

Abstract: In this study we present a steady-state adaptation of the thermodynamically motivated stress fiber (SF) model of Vigliotti et al. (2015). We implement this steady-state formulation in a non-local finite element setting where we also consider global conservation of the total number of cytoskeletal proteins within the cell, global conservation of the number of binding integrins on the cell membrane, and adhesion limiting ligand density on the substrate surface. We present a number of simulations of cell spreadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 22 publications
1
34
0
Order By: Relevance
“…Such a competition allows for the identification of a low free-energy state, and it is shown that the predicted cell areas and SF alignments in these configurations are similar to reported experimental measurements (14). However, in the study of McEvoy et al (13), a single low-energy spread state is identified. This deterministic approach neglects the fact that cells display a fluctuating response to their microenvironment in terms of observables such as SF alignment and spread area.…”
Section: Introductionsupporting
confidence: 56%
See 4 more Smart Citations
“…Such a competition allows for the identification of a low free-energy state, and it is shown that the predicted cell areas and SF alignments in these configurations are similar to reported experimental measurements (14). However, in the study of McEvoy et al (13), a single low-energy spread state is identified. This deterministic approach neglects the fact that cells display a fluctuating response to their microenvironment in terms of observables such as SF alignment and spread area.…”
Section: Introductionsupporting
confidence: 56%
“…under the constraint that the cell maintains a homeostatic state. In previous studies, the importance of considering the system free energy in the interpretation of cell-spreading behavior has been recognized (13,29). McEvoy et al (13) identified low (or minimal) free-energy cell spread states within a limited phase space of axisymmetric configurations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations